Гипотеза о социальных механизмах возникновения моногамной половой любви - Паниотто, В. (Социология: теория, методы, маркетинг, 2004)
The author considers that the monogamous marriage dominant in the majority of modern countries is supported due to social but not biological factors (the primates,predecessors of humans, were not monogamous). The main idea is to show that love is asocial and psychological mechanism developed for protection and support of monogamy; it makes the norms regulating monogamous behavior more efficient.